2015
DOI: 10.1093/bjsw/bcv127
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Intervention in a Continuous Shared Traumatic Reality: An Example from the Israeli–Palestinian Conflict

Abstract: Growing political instability around the world has exposed an increasing number of communities to military conflict. Social workers and other mental health professionals who work as trauma workers, and who both live and practise within these communities, are doubly exposed: directly and indirectly, personally and professionally. The present study examined the consequences on trauma workers and on the therapeutic process itself of working in a continuous Shared Traumatic Reality. The study was based on content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
(36 reference statements)
0
12
0
Order By: Relevance
“… Professional training. Over the years, it has become clear that the impact of disasters and war circumstances has increasingly complicated the tasks of professionals involved in therapeutic interventions in an ongoing traumatic reality ( Dekel and Baum, 2010 ; Lavi et al, 2017 ). The knowledge accumulated to date indicates a need to address this complexity already during professional training, emphasizing specialized training in dealing effectively with emergencies.…”
Section: The Treatment Levelmentioning
confidence: 99%
“… Professional training. Over the years, it has become clear that the impact of disasters and war circumstances has increasingly complicated the tasks of professionals involved in therapeutic interventions in an ongoing traumatic reality ( Dekel and Baum, 2010 ; Lavi et al, 2017 ). The knowledge accumulated to date indicates a need to address this complexity already during professional training, emphasizing specialized training in dealing effectively with emergencies.…”
Section: The Treatment Levelmentioning
confidence: 99%
“…Several studies on the effects of working in a shared war reality have reported a decrease in perceived professional competence among MHPs [5] and a sense of being deskilled [3]. However, other studies reveal a strong perception of professional competence [19] and high levels of professional confidence [9] among these MHPs.…”
Section: Introductionmentioning
confidence: 99%
“…Post-traumatic growth also has been reported among nurses working in a shared war-related reality in Israel [10] and in Gaza [15]. Positive consequences also can include heightened intimacy in the therapeutic relationship [4,20], a strong therapeutic alliance [19], a high level of work satisfaction, and a sense of agency and helpfulness [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations